An Analysis Of Reliability Protection Systems At PLTU PT. Indah Pontjan - Senri Kamsianto Naibaho; Dicky Lesmana; Rahmaniar, Rahmaniar (Jurnal Scientia, 2024)
In this research, the aim is to analyze the reliability of the protection system at the Steam Power Plant (PLTU) at PT. Indah Pontjan. The protection system is a crucial component in PLTU operations, which functions to protect equipment and systems from interference and ensure operational safety. In this research, the reliability evaluation method is used to assess the effectiveness of the existing protection system. Analysis is carried out through operational data collection, protection system inspection, and simulation of various disturbance scenarios. The research results show that the reliability of the protection system at PLTU PT. Indah Pontjan already meets industry standards, but there are still several areas that require improvement. Some important findings include the detection of discrepancies in protection coordination, the need for improved protection devices, and the importance of further training for system operators. Recommendations are provided to strengthen the protection system, including the addition of modern protection devices, increased routine maintenance, and implementation of regular training programs. By increasing the reliability of the protection system, it is hoped that PLTU PT. Indah Pontjan can operate more safely and efficiently, reducing the risk of equipment damage and minimizing operational downtime. This research makes an important contribution to the development of a more reliable and effective protection system for the steam power generation industry.